The treatment of patients with local stages I, II, IE, IIE of Hodgkin's lymphoma: medical radiological research center experience - S. V. Shakhtarina; V. V. Pavlov; A. A. Danilenko; N. V. Afanasova (Онкогематология, 2022)
In this article we present results of radiotherapy and combined modality treatment of 1882previously untreated patients with Hodgkin s lymphoma (HL) stages I, II, Ie, IIe at MRRC RAMS (Obninsk) between 1968 and 2006. Frequency and types of second malignancies, female fertility are presented too. 25-years overall survival rate was 59,1%, disease-specific survival — 73,2%, freedom from treatment failure — 46,8% after the radical program of radiotherapy. These rates in female patients with HL stages IA, IIA and histological subtype nodular sclerosis resulted 86,5%, 93,7%, 82,2% respectively. 20-years overall survival rate was 80,7%, disease-specific survival — 85,1%, freedom from treatment failure — 81,1% after combined modality treatment. In favorable prognosis group 36-month overall survival was 100% with no recurrences after 6 cycles of chemotherapy COPP followed by radiotherapy in total doses of20—24Gy. In intermediate prognosis group overall and disease-specific survival were 97,1%, freedom from treatment failure survival — 84,1% after 6—8 cycles ABVD followed by involved field radiotherapy in total doses 36Gy.